New energy automobile power battery thermal runaway wreckage extraction and cause judgment method

Through the systematic extraction and analysis of thermal runaway wreckage of power batteries in new energy vehicles, the problem of difficulty in determining the cause of thermal runaway batteries in the existing technology is solved, and accurate investigation and cause judgment of fire accidents are achieved.

CN119438522AActive Publication Date: 2025-02-14GUANGZHOU INST OF ENERGY TESTING

Patent Information

Application Number
CN202411573508.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively determine the cause of thermal out-of-control of new energy vehicle power batteries, resulting in a lack of targeted methods and technical means in fire accident investigations.

Method used

Through investigation and sampling, separation and extraction of debris substances, copper current collector structure analysis, X-ray powder diffraction testing and Raman spectroscopy analysis, the debris of the power battery electrodes are systematically extracted and analyzed, and their components and structural changes are determined, thereby judging thermal runaway. cause.

Benefits of technology

It has achieved effective extraction and cause judgment of thermal runaway wreckage of new energy vehicle power batteries, improved the accuracy and efficiency of fire accident investigation, and is suitable for investigation of fire accidents caused by thermal runaway in various lithium-ion battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438522A_ABST
    Figure CN119438522A_ABST
Patent Text Reader

Abstract

The invention discloses a new energy automobile power battery thermal runaway wreckage extraction and cause judgment method. The method mainly comprises a survey sampling step, a wreckage extraction step, a wreckage current collector structure analysis step, a wreckage material powder crystal form structure analysis step and a material carbon component analysis step. According to the method, new energy automobile fire accident field investigation and laboratory analysis and detection technologies are systematically combined together, technical support is provided for analysis and detection of power battery wreckage in fire accident investigation, and an existing new energy automobile fire accident investigation system is effectively improved; and related accident investigators can conveniently carry out new energy automobile fire accident investigation and effective judgment of accident causes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a battery thermal runaway judgment technology, and in particular to a method for extracting thermal runaway debris and judging the cause of a power battery of a new energy vehicle. Background Art

[0002] From 2020 to 2023, the penetration rate of new energy vehicles in China has climbed from 5.4% to 31.6%, and this trend is expected to continue to grow in 2024, approaching a penetration rate of 40%. However, new energy vehicle fire accidents have occurred frequently in recent years. According to statistics from the emergency management department, the spontaneous combustion rate rose by 32% in the first quarter of 2023, with an average of 8 new energy vehicles catching fire every day.

[0003] The importance of investigating new energy vehicle fire accidents is self-evident. With the improvement of environmental awareness and the advancement of science and technology, new energy vehicles have become an important development direction of the automotive industry. However, fire is one of the potential safety risks of new energy vehicles. Once it occurs, it will not only endanger the lives of passengers, but also cause major property losses and affect the public's confidence in new energy vehicles. In-depth investigation of new energy vehicle fire accidents can accurately locate the cause of the accident, whether it is caused by battery technology defects, charging facility problems, improper use or external collisions. This is crucial for subsequent technical improvements, the formulation of safety standards and the improvement of regulatory policies. Therefore, strengthening the investigation of new energy vehicle fire accidents is the cornerstone of ensuring public safety and promoting the sustainable development of the new energy vehicle industry.

[0004] The structure of power batteries for new energy vehicles is complex and sophisticated, mainly consisting of multiple battery modules, thermal management systems, battery management systems, electrical systems and structural parts. Among them, the battery cell is the basic energy storage unit of the power battery, consisting of a positive electrode, a negative electrode, a diaphragm and an electrolyte. Transition metal oxides such as cobalt, nickel, manganese and iron are often used for the positive electrode, and graphite is used for the negative electrode. The electrolyte is responsible for ion conduction and can be liquid or solid. The battery module is composed of the above-mentioned multiple battery cells connected in series or in parallel to achieve the required voltage and capacity. The module also contains conductive connectors, plastic frames, cooling systems, etc. Different battery cells in the power battery that experienced the same fire accident may have different causes for their thermal runaway. The first battery cell that ignites may be spontaneous combustion caused by external abnormal effects. The other battery cells around it will be subjected to thermal runaway caused by the high temperature heat transmitted from it or open flames. However, at present, the main method of investigating the wreckage of power batteries in new energy vehicle fire accidents is on-site visual observation. For example, after disassembling the battery accident module, observe the top cover and side panels of the single body, whether there is mutual extrusion and deformation between the battery cells, arching of the pole pieces, and whether there is arcing and melting through the single body shell to infer the cause of the accident. There is still a lack of more effective technology for extracting the wreckage of thermal runaway power batteries of new energy vehicles and determining the cause. The method of sampling the internal materials of the wreckage of power batteries after fire accidents and the subsequent analysis technology need to be improved urgently. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art, provide a method for extracting thermal runaway debris from power batteries of new energy vehicles and determining the cause, effectively determine the cause of thermal runaway of the corresponding power battery cells, and provide technical support for the effective determination of the cause of fire accidents of new energy vehicles.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A method for extracting debris from thermal runaway of a power battery of a new energy vehicle and determining the cause of the thermal runaway, the method comprising:

[0008] Investigate sampling procedures to obtain battery electrodes after fire incidents;

[0009] The debris extraction step is to separate and extract the debris materials of the battery pole pieces obtained in the investigation and sampling step, so as to separate the battery pole piece debris that has experienced the fire accident according to different main material components and obtain battery pole piece debris with different particle sizes.

[0010] a step of analyzing the structure of the residual current collector, screening out the battery pole piece debris that meets a first particle size value from the battery pole piece debris of different particle sizes, wherein the battery pole piece debris that meets the first particle size value is a copper current collector, treating the copper current collector, observing the structure of the treated copper current collector with a metallographic microscope, and analyzing the metallographic microstructure of the copper foil to analyze the cause of the thermal runaway accident;

[0011] The step of analyzing the crystal structure of the powder of the debris material is to select the battery pole pieces that meet the second particle size value from the battery pole pieces of different particle sizes to carry out X-ray powder diffraction test, and analyze the conditions that have caused thermal runaway based on the test spectrum;

[0012] The material carbon component analysis step is to select the battery pole piece debris that meets the third particle size value from the battery pole piece debris of different particle sizes for Raman spectroscopy analysis, and analyze and infer the thermal runaway conditions that have occurred based on the Raman spectrum.

[0013] Optionally, the survey sampling step includes:

[0014] Remove the power battery pack that has experienced the fire accident from the vehicle, cut off the electrical connection lines, and then disassemble the battery pack;

[0015] Observe the burned area, remove the most severely burned module, dismantle the module casing, and take out the internal battery cells;

[0016] Observe the deformation characteristics of the entire battery cell group inside the module, and remove the battery cell that is most severely squeezed and deformed in the module or the battery cell that is initially determined to be the trigger point through fire trace analysis at the accident site;

[0017] Remove the single body shell, take out the pole piece at the location with severe burning inside, and if the burning situation is not much different, take out the pole piece in the area with the most serious extrusion and deformation; if the accident power battery has been extinguished with fire water, first remove the particulate matter remaining on the pole piece, and then take out the pole piece at the location with severe burning inside.

[0018] Optionally, the battery pole pieces obtained in the investigation and sampling step are subjected to material separation and extraction of the debris, so as to separate the battery pole piece debris that has experienced the fire accident according to different main material components to obtain battery pole piece debris of different particle sizes, including:

[0019] Soak the battery pole pieces after the fire accident in a 30℃~35℃, 50%~70% concentration ethanol solution, and adjust the solution pH value to 6.0±0.5 with acetic acid; after soaking for 2~3 hours, filter, and rinse with anhydrous ethanol and ionized water alternately for no less than 3 times until the filtrate pH value is about 7.0;

[0020] The battery pole piece after the above treatment is transferred to a vacuum oven and dried at 50°C to 80°C and a relative vacuum degree of 0.06 to 0.09 MPa for 24 hours to ensure that the pole piece debris is completely dried;

[0021] The dried block-shaped battery pole pieces are transferred into a planetary ball mill, agate grinding beads are placed in the mill, and the powder and flake-like loose pole piece debris samples are obtained at a speed of 100 r / min to 150 r / min for 1 to 2 hours. Then, a vertical multi-layer screening method is used to screen the loosely dispersed pole piece debris from top to bottom in the order of 20 mesh, 30 mesh, 50 mesh, 60 mesh or 80 mesh, and the loosely dispersed pole piece debris are separated according to the particle size of ≥0.9 mm, 0.9 mm to 0.6 mm, 0.6 mm to 0.355 mm, 0.355 to 0.3 mm or 0.3 to 0.2 mm.

[0022] Optionally, the processing of the copper current collector includes:

[0023] The black positive / negative electrode materials remaining on the surface of the copper current collector are wiped off, and then transferred to anhydrous ethanol, and the remaining black substances on the surface of the copper current collector are cleaned by ultrasonic dispersion. The cleaned copper current collector is moved to a vacuum oven for drying; the surface of the dried copper current collector is polished.

[0024] Optionally, the analysis of the cause of the thermal runaway accident by metallographic microstructure analysis of the copper foil includes:

[0025] If circular black spots are found on the copper foil through observation, it is caused by a high current breakdown process; if the area of ​​the circular black spots is smaller than the preset value and appears densely, it is judged that thermal runaway caused by overcharging has occurred there;

[0026] If there are small dendrites or equiaxed crystals in a location in the copper foil, and large equiaxed crystals are scattered around other locations, it means that this location has experienced the highest temperature during the thermal runaway process and is also the location where the temperature drops the earliest and the drop rate is the fastest. Therefore, it is judged that this location is the initiation site of the local internal short circuit.

[0027] If there are colorful ring patterns in the copper foil, it is the trace left by the initial flame burning, which means that there has been thermal runaway caused by open flames.

[0028] If the copper foil shows an overall uniform color change, it is judged that the area has been heated and overheated, causing thermal runaway.

[0029] Optionally, the screening out of battery pole piece debris meeting the second particle size value and conducting X-ray powder diffraction testing includes:

[0030] The battery pole piece powder residues on the 30-mesh or 50-mesh test sieve are screened out for X-ray powder diffraction testing. The scanning angle range during the test must be at least 20° to 43°.

[0031] Optionally, analyzing the thermal runaway-inducing conditions that have occurred according to the test map includes:

[0032] If the relative intensity of the newly added peaks in the range of 21° to 24° is close, the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, the relative intensity of the newly added peaks from low angle to high angle in the range of 33° to 35° shows an increasing trend first and then decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 38° to 43° shows a decreasing trend first and then increasing trend as a whole, it is judged that thermal runaway caused by overcharging has occurred at this location;

[0033] If the relative intensity of the newly added peaks from low angle to high angle in the range of 21° to 24° shows an overall trend of increasing first and then decreasing, the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angle to high angle in the range of 33° to 35° shows an overall trend of decreasing first and then increasing, and the relative intensity of the newly added peaks from low angle to high angle in the range of 38° to 43° shows an overall trend of approaching, it is judged that thermal runaway caused by local internal short circuit has occurred at this location;

[0034] If the relative intensity of the newly added peaks from low angle to high angle in the range of 21° to 24° shows a decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, and the relative intensity of the newly added peaks in the range of 33° to 35° is close, and the relative intensity of the newly added peaks in the range of 38° to 43° is close, it is judged that thermal runaway caused by fire has occurred at this location;

[0035] If the relative intensity of the newly added peaks from low angles to high angles in the range of 21° to 24° shows an overall trend of first increasing and then decreasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° shows an overall trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° shows an overall trend of decreasing, it is judged that thermal runaway caused by overheating has occurred at this location.

[0036] Optionally, the screening out battery pole piece debris meeting the third particle size value and conducting Raman spectroscopy analysis includes:

[0037] The battery pole powder residues on the 60-mesh or 80-mesh test sieve were screened out for Raman spectroscopy analysis. -1 and 1580±10cm -1The carbon Raman active peaks that appear nearby are the objects of analysis and research, which correspond to the D peak of amorphous carbon structure and the G peak of graphitized carbon respectively. The relative ratio of the intensity of the G peak to the intensity of the D peak is used to analyze and infer the conditions that caused thermal runaway that occurred there.

[0038] Optionally, analyzing and inferring the thermal runaway-inducing conditions that have occurred at the location based on the relative ratio of the intensity of the G peak to the intensity of the D peak includes:

[0039] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 1 and 2, it is judged that thermal runaway caused by a local internal short circuit has occurred at that location;

[0040] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 3 and 5, it is judged that thermal runaway caused by overheating has occurred at this location;

[0041] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 6 and 9, it is judged that thermal runaway caused by overcharging has occurred at this location;

[0042] If the relative ratio of the intensity of peak G to the intensity of peak D is greater than 10, it is judged that thermal runaway caused by fire has occurred at that location.

[0043] Optionally, the vertical multi-layer screening method refers to stacking a series of standard sieves with different apertures or different mesh sizes vertically from top to bottom in the order of decreasing aperture or increasing mesh size for screening.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The method for extracting thermal runaway debris and determining the cause of new energy vehicle power battery thermal runaway provided by the present invention systematically combines the on-site investigation of new energy vehicle fire accidents with laboratory analysis and detection technology, providing technical support for the analysis and detection of power battery debris in fire accident investigations, and effectively improving the current new energy vehicle fire accident investigation system, making it easier for relevant accident investigators to conduct new energy vehicle fire accident investigations and effectively determine the causes of accidents.

[0046] (2) The present invention provides a method for extracting and determining the cause of thermal runaway debris of power batteries for new energy vehicles, and invents a power battery debris extraction technology. After battery disassembly, monomer selection, debris electrode sampling, impurity removal, alcohol solution immersion to remove fire liquid, ball milling and vertical multi-layer screening, the battery electrode debris that has experienced a fire accident can be effectively separated according to different main material components, solving the problem of difficulty in extracting materials for analysis and research after sintering the battery electrode after a fire accident. The method is suitable for investigations of various fire accidents caused by thermal runaway of lithium-ion battery systems, and has the characteristics of easy operation, high efficiency and strong applicability.

[0047] (3) The existing technology for determining the fire point of new energy vehicle power battery is mostly to first look at the battery operation data recorded in the whole vehicle operation, including checking the battery charging current, the highest temperature, lowest temperature, highest voltage, lowest voltage, and insulation resistance value of the battery cell, and predicting which condition caused the fire through the characteristics of these data, and then dismantling the battery pack on site, observing the structure of the battery cell, and judging which battery cell is squeezed to be the fire point. The method for extracting the thermal runaway debris of the new energy vehicle power battery and determining the cause of the fire provided by the present invention is based on the metallographic analysis technology of the residual copper current collector, the material crystal structure analysis technology, and the material carbon composition analysis technology, and clarifies the image features or parameter thresholds for determining different triggering methods. It is of great significance to improve the effectiveness of the investigation of the cause of new energy vehicle fire accidents and study the occurrence law of new energy vehicle fires. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A flow chart of a method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery provided by an embodiment of the present invention;

[0049] Figure 2 These are photos of sampling conditions in Application Example 1 of the present invention, including a single-body sampling condition diagram (a) and a pole piece sampling condition diagram (b).

[0050] Figure 3 This is a schematic diagram of the vertical multi-layer screening method in Application Example 1 of the present invention (a), a photo of the substance separated and extracted by a 20-mesh standard sieve (b1), a scanning electron microscope picture of the material (b2), and an elemental energy spectrum diagram of the material (b3), a photo of the substance separated and extracted by a 50-mesh standard sieve (c1), a scanning electron microscope picture of the material (c2), and an elemental energy spectrum diagram of the material (c3), and a photo of the substance separated and extracted by an 80-mesh standard sieve (d1), a scanning electron microscope picture of the material (d2), and an elemental energy spectrum diagram of the material (d3).

[0051] Figure 4 It is a metallographic microscope picture of the current collector debris in Application Example 1 of the present invention, including the metallographic microstructure of the pole piece current collector at the sampling position (a) and the metallographic microstructure of the current collector at the comparison position (b).

[0052] Figure 5 It is the X-ray powder diffraction spectrum of the battery debris material in Application Example 1 of the present invention (a), the X-ray powder diffraction spectrum of the normal battery positive electrode material (b), the X-ray powder diffraction spectrum of the normal battery negative electrode material (c) and the X-ray powder diffraction spectrum of copper (d).

[0053] Figure 6 This is the Raman spectrum of the battery debris in Application Example 1 of the present invention.

[0054] Figure 7 These are photos of sampling conditions in Application Example 2 of the present invention, including a single-body sampling condition diagram (a) and a pole piece sampling condition diagram (b).

[0055] Figure 8 These are the photograph (a1) of the substance separated and extracted by a 20-mesh standard sieve after screening by the vertical multi-layer screening method, the scanning electron microscope picture (a2) of the material, and the element energy spectrum (a3) ​​of the material; the photograph (b1) of the substance separated and extracted by a 50-mesh standard sieve, the scanning electron microscope picture (b2) of the material, and the element energy spectrum (b3) of the material; and the photograph (c1) of the substance separated and extracted by an 80-mesh standard sieve, the scanning electron microscope picture (c2) of the material, and the element energy spectrum (c3) of the material.

[0056] Fig. 9 This is a metallographic microscope picture of the current collector debris in Application Example 2 of the present invention.

[0057] Fig.10 This is the X-ray powder diffraction spectrum of the battery debris material in Application Example 2 of the present invention.

[0058] Fig.11 This is the Raman spectrum of the battery debris in Application Example 2 of the present invention.

[0059] Fig.12 These are photos of sampling conditions in Application Example 3 of the present invention, including a single-body sampling condition diagram (a) and a pole piece sampling condition diagram (b).

[0060] Fig.13 These are the photograph (a1) of the substance separated and extracted by a 20-mesh standard sieve after screening by the vertical multi-layer screening method, the scanning electron microscope picture (a2) of the material, and the element energy spectrum (a3) ​​of the material; the photograph (b1) of the substance separated and extracted by a 50-mesh standard sieve, the scanning electron microscope picture (b2) of the material, and the element energy spectrum (b3) of the material; and the photograph (c1) of the substance separated and extracted by an 80-mesh standard sieve, the scanning electron microscope picture (c2) of the material, and the element energy spectrum (c3) of the material.

[0061] Fig.14 This is a metallographic microscope picture of the current collector debris in Application Example 3 of the present invention.

[0062] Fig.15 This is the X-ray powder diffraction spectrum of the battery debris material in Application Example 3 of the present invention.

[0063] Fig.16 This is the Raman spectrum of the battery debris in Application Example 3 of the present invention.

[0064] Fig.17 This is a photo of the sampling situation in Application Example 4 of the present invention.

[0065] Fig.18 These are the photograph (a1) of the substance separated and extracted by a 20-mesh standard sieve after screening by the vertical multi-layer screening method, the scanning electron microscope picture (a2) of the material, and the element energy spectrum (a3) ​​of the material; the photograph (b1) of the substance separated and extracted by a 50-mesh standard sieve, the scanning electron microscope picture (b2) of the material, and the element energy spectrum (b3) of the material; and the photograph (c1) of the substance separated and extracted by an 80-mesh standard sieve, the scanning electron microscope picture (c2) of the material, and the element energy spectrum (c3) of the material.

[0066] Fig.19 This is a metallographic microscope picture of the current collector debris in Application Example 4 of the present invention.

[0067] Fig. 20 It is the X-ray powder diffraction spectrum of the battery debris material in Application Example 4 of the present invention.

[0068] Fig.21 This is the Raman spectrum of the battery debris in Application Example 4 of the present invention. DETAILED DESCRIPTION

[0069] Example:

[0070] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0071] See also Figure 1 As shown, the method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery provided in this embodiment mainly includes the following steps:

[0072] Investigate the sampling steps to obtain battery pole pieces after a fire incident, including:

[0073] Remove the power battery pack from the vehicle after the fire accident, cut off the electrical connection lines at all places, and then disassemble the battery pack. Observe the fire area, remove the module with the most serious burn damage, remove the module shell, and remove the internal battery cells; observe the deformation change characteristics of the entire group of battery cells inside the module, remove the battery cells that are most severely squeezed and deformed in the module or the battery cells at the initial triggering point preliminarily determined by the fire trace analysis at the accident scene; remove the monomer shell, if the accident power battery has been extinguished by fire water, hard foam particles often remain on the pole piece, then use tools to remove the above-mentioned granular substances first, the hard foam particles are obvious white, yellow, yellow-white, brown or other colored foam particles, salt particles or crystalline substances of the same type left by the fire water on the pole piece, the tools used can be tweezers, pliers, clamps, brushes and other tools that can remove hard foam particles, etc., if there is no fire extinguishing by fire water, this step can be skipped; remove the pole piece in the internal severely burned position, and remove the pole piece in the most severely squeezed and deformed area when the burning situation is not much different, and the amount removed can be determined according to the actual situation. The area of ​​the electrode removed is not less than 2cm 2 , with a thickness of no less than 3mm. When sampling the battery cell pole fragments, multiple areas can be selected for sampling and analysis based on the fire situation. Power batteries are mainly lithium-ion batteries.

[0074] The debris extraction step is to separate and extract the debris materials of the battery pole pieces obtained in the investigation and sampling step, so as to separate the battery pole piece debris that has experienced the fire accident according to different main material components and obtain battery pole piece debris of different particle sizes, specifically including:

[0075] The battery pole pieces obtained from the accident site investigation and sampling in the investigation and sampling step are used to separate and extract the debris materials in the laboratory. Due to the fire process, the diaphragm is melted, the positive aluminum current collector is melted out, and various organic matters are carbonized. At this time, the pole pieces often appear in the form of sintered blocks. The alcohol solution immersion method is used to remove the residual substances of the fire-fighting fluid, surfactants, oil stains, etc. That is, the treated pole pieces are immersed in an ethanol solution with a concentration of 50% to 70% at 30°C to 35°C, and the pH value of the solution is adjusted to 6.0±0.5 with acetic acid to remove the residual substances of the fire-fighting fluid, surfactants, oil stains, etc.; after soaking for 2 to 3 hours, filter, and then rinse with anhydrous ethanol and deionized water alternately for no less than 3 times until the pH value of the filtrate is about 7.0. In this step, the purpose of filtration is to remove the residual fire-fighting fluid so as not to affect the subsequent analysis. If the fire is not extinguished with fire water, filtration is not required. After rinsing with anhydrous ethanol and deionized water alternately for no less than 3 times, follow the subsequent steps.

[0076] Transfer the above-treated electrode to a vacuum oven and dry it at 50℃~80℃ and 0.06~0.09Mpa relative vacuum for 24 hours to ensure that the electrode debris is completely dried. Transfer the above-dried block electrode to a planetary ball mill, put in agate grinding beads, and grind and disperse at a speed of 100r / min~150r / min for 1~2 hours to obtain a loose electrode debris sample with coexistence of powder and flakes. Of course, you can also put the dried block electrode into a mortar and use manual grinding and dispersion to obtain a loose electrode debris sample with coexistence of powder and flakes.

[0077] Then, a vertical multi-layer screening method is used to screen from top to bottom with mesh sizes of 20, 30, 50, 60 or 80, and the loosely dispersed pole piece debris is separated according to the particle size into ≥0.9mm, 0.9mm-0.6mm or 0.6mm-0.355mm, 0.355-0.3mm or 0.3-0.2mm for subsequent testing and analysis. The above-mentioned different particle size distribution areas correspond to different main components. The size diameter ≥0.9mm is mainly sheet-like current collector materials. The materials less than 0.9mm are mainly black powders of positive electrode materials, negative electrode materials and carbonized materials. Since the positive electrode materials are transition metal oxides such as cobalt, nickel, manganese, and iron, they are often sintered into larger blocks after experiencing a fire. Therefore, the carbonized materials collected in the two particle size intervals of 0.9mm-0.6mm and 0.6mm-0.355mm often contain higher positive electrode material components. After the fire, the binder between the negative electrode graphite materials is completely carbonized, and the combined effects of heat, force and gas during the fire cause the graphite particles to pulverize and disperse. Therefore, the materials obtained in the particle size range of 0.355-0.3mm and 0.3-0.2mm contain more carbon. Next, the different materials screened out according to the particle size are tested and analyzed in turn. It should be noted that the "vertical multi-layer screening method" refers to a series of standard sieves with different apertures or different mesh numbers stacked vertically from top to bottom in the order of decreasing aperture or increasing mesh number for screening. The number, aperture or mesh number of the standard sieves used can be adjusted according to actual needs. The "positive electrode material" refers to the positive electrode material commonly used in power ion batteries, including nickel cobalt manganese oxide lithium positive electrode material, lithium iron phosphate positive electrode material, etc. The "negative electrode material" refers to the negative electrode material commonly used in power ion batteries, including graphite materials, etc.

[0078] Thus, in this step, the power battery wreckage is extracted, and after battery disassembly, monomer selection, wreckage pole piece sampling, impurity removal, alcohol solution immersion to remove fire liquid method, ball milling pulverization and vertical multi-layer screening method, the battery pole piece wreckage that has experienced a fire accident can be effectively separated according to different main material components, solving the problem that it is difficult to extract materials for analysis and research in a targeted manner after the battery pole pieces are sintered after a fire accident. It is suitable for investigations of various fire accidents caused by thermal runaway of lithium-ion battery systems, and has the characteristics of easy operation, high efficiency and strong applicability.

[0079] The step of analyzing the structure of the residual current collector is to screen out the battery pole piece debris that meets the first particle size value, wherein the battery pole piece debris that meets the first particle size value is a copper current collector, and the copper current collector is processed, and the structure of the processed copper current collector is observed using a metallographic microscope, and the cause of the thermal runaway accident is analyzed by metallographic microstructure analysis of the copper foil, specifically including:

[0080] Take the pole piece debris on the 20-mesh test sieve in the debris extraction step for testing. The particle size of the pole piece debris here is ≥0.9mm, mostly broken, flaky copper current collectors, and there are still a lot of black positive / negative electrode materials remaining on the copper current collector. Take the above current collector and first wipe it with a soft brush to remove the large pieces of black positive / negative electrode material remaining on the surface. Then, transfer it to anhydrous ethanol and ultrasonically disperse and clean the remaining black material on the surface of the copper foil for 1 hour. Transfer the above-treated pole piece to a vacuum oven and dry it at 50°C and 0.08-0.09Mpa relative vacuum for 2 hours to ensure that the current collector is thoroughly dried. Finally, after polishing the surface of the copper foil with non-woven fabric, use a metallographic microscope to observe the structure, and analyze the cause of the thermal runaway accident through metallographic microstructure analysis of the copper foil. The analysis and judgment method is as follows:

[0081] If circular black spots are found on the copper foil through observation, it is caused by a high current breakdown process. If the circular black spots are small in area and appear densely, it is judged that thermal runaway caused by overcharging has occurred there. "Overcharging" includes charging the power battery with a charge exceeding the rated capacity or acceptable charging range of the battery and charging the power battery so that the voltage continues to rise and exceeds the rated operating voltage of the battery.

[0082] If there are small dendrites or equiaxed crystals in a location in the copper foil, and large equiaxed crystals are scattered around other locations, it indicates that this location has experienced the highest temperature during the thermal runaway process and is also the location where the temperature drops first and the drop rate is the fastest. Therefore, it can be judged that this location is the initiation site of a local internal short circuit.

[0083] If a colorful ring pattern appears in the copper foil, it is a trace left by the initial flame burning, which means that thermal runaway caused by open flame has occurred there; "open flame" includes open flames ignited intentionally or unintentionally by the accident perpetrator, fire in the car's wiring harness, electrical appliances or interior, and open flames caused by thermal runaway in other battery cells.

[0084] If the copper foil changes color evenly, such as turning red, reddish brown or black, it is judged that the area has been overheated and caused thermal runaway. The "overheating caused by heat" mentioned above includes the target power battery cell being heated by a high-temperature heat source other than an open flame, including cars operating at abnormally high temperatures, the first battery cell to experience thermal runaway, and high heat sources generated by high-voltage arcing, etc.

[0085] The crystal structure analysis step of the powder of the debris material is to screen out the battery pole pieces that meet the second particle size value for X-ray powder diffraction testing, and analyze the conditions that have caused thermal runaway based on the test spectrum, including:

[0086] When a lithium-ion battery experiences thermal runaway, a series of chemical reactions will occur inside to generate a large amount of heat and gas, accompanied by the melting of the positive electrode current collector and diaphragm materials at high temperatures, and the decomposition of the positive electrode materials and binders under the action of the electrolyte. After thermal runaway, various materials inside the battery debris are sintered and mixed together, presenting a highly mixed crystal form. These material crystal form characteristics can be used to identify the high-temperature thermal runaway process experienced by the material. The positive electrode material changes from the original monodisperse particle structure to a sintered block structure. There is also a situation where it is difficult to peel off the graphite negative electrode carbon material due to co-agglomeration. In the process of detecting its crystal structure, if there is too much graphite phase, the ultra-high carbon X-ray diffraction peak will cover up the newly added characteristic peaks related to other positive electrode materials, thereby seriously affecting the analysis of the test results. Therefore, in order to obtain components containing more positive electrode materials for crystal structure analysis, it is necessary to take the powder residue on the 30-mesh or 50-mesh test sieve in (2) for X-ray powder diffraction test (XRD). During the test, the scanning angle (2θ) range must at least include 20° to 43°, and the specific scanning angle range can be selected according to the test needs. In the four angle ranges of 21° to 24°, 29° to 32°, 33° to 35° and 38° to 43° on the XRD test spectrum, each of the above angle ranges may produce multiple new characteristic peaks. According to the relative intensity characteristics of each group of new series of diffraction peaks, the thermal runaway conditions that have occurred at this location are analyzed and inferred. Taking the ternary positive electrode material system as an example, the analysis and judgment method is as follows:

[0087] If the relative intensity of the newly added peaks in the range of 21° to 24° is close, the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, the relative intensity of the newly added peaks from low angle to high angle in the range of 33° to 35° shows an increasing trend first and then decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 38° to 43° shows a decreasing trend first and then increasing trend as a whole, it is judged that thermal runaway caused by overcharging has occurred at this location;

[0088] If the relative intensity of the newly added peaks from low angles to high angles in the range of 21° to 24° shows an overall trend of first increasing and then decreasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° shows an overall trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° shows an overall trend of approaching, it is judged that thermal runaway caused by local internal short circuit has occurred at this location; the "local internal short circuit" includes the entry of foreign objects into the power battery, resulting in local micro-short circuit, partial puncture or complete puncture of the battery, including internal short circuits caused by lithium dendrites caused by internal defects in the power battery, etc.

[0089] If the relative intensity of the newly added peaks from low angle to high angle in the range of 21° to 24° shows a decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, and the relative intensity of the newly added peaks in the range of 33° to 35° is close, and the relative intensity of the newly added peaks in the range of 38° to 43° is close, it is judged that thermal runaway caused by fire has occurred at this location;

[0090] If the relative intensity of the newly added peaks from low angles to high angles in the range of 21° to 24° shows an overall trend of first increasing and then decreasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° shows an overall trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° shows an overall trend of decreasing, it is judged that thermal runaway caused by overheating has occurred at this location.

[0091] It should be noted that the above method can be used to establish data change characteristics for different battery material systems, that is, to analyze and infer the thermal runaway conditions that have occurred there based on the relative intensity characteristics of each new series of diffraction peaks.

[0092] The material carbon component analysis step is to screen out the battery pole pieces that meet the third particle size value for Raman spectroscopy analysis, and to analyze and infer the thermal runaway conditions that have occurred based on the Raman spectrum, including:

[0093] The carbon components in the debris are mainly graphite negative electrode materials and carbonization products of other organic substances such as macromolecules and polymers in the battery. Therefore, the carbon components that experience different thermal runaway processes will present different molecular structures. Take the powder debris on the 60-mesh or 80-mesh test sieve in (2) and conduct Raman spectroscopy analysis. -1 and 1580±10cm -1 The carbon Raman active peaks that appear nearby are the objects of analysis and research, corresponding to amorphous carbon (D peak) and graphitized carbon (G peak). Based on the relative ratio of the intensity of the G peak to the intensity of the D peak, we can analyze and infer the conditions that caused thermal runaway that occurred there. The analysis and judgment methods are as follows:

[0094] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 1 and 2, it is judged that thermal runaway caused by a local internal short circuit has occurred at that location;

[0095] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 3 and 5, it is judged that thermal runaway caused by overheating has occurred at this location;

[0096] If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 6 and 9, it is judged that thermal runaway caused by overcharging has occurred at this location;

[0097] If the relative ratio of the intensity of peak G to the intensity of peak D is greater than 10, it is judged that thermal runaway caused by fire has occurred at that location.

[0098] In the actual thermal runaway initiation process, it is possible that multiple factors are superimposed and jointly initiated. The above method can be used to conduct a comprehensive analysis of the analysis results of materials with different particle sizes.

[0099] The method of the present invention is further described below in conjunction with several application examples:

[0100] Application Example 1:

[0101] Taking a power battery thermal runaway accident as an example, the extraction and analysis of the power battery monomer wreckage are as follows:

[0102] like Figure 2 As shown, the battery cell that was initially identified as the trigger point by fire trace analysis was taken out from the accident scene. Figure 2 (a) It can be seen that the surface of the battery cell is covered with residual hard foam particles of fire-fighting liquid. After removing the cell shell and cleaning the surface residue of fire-fighting liquid with tweezers and a brush, the deformation and extrusion direction of the cell pole piece inside the battery is visually observed. Figure 2 The arrow in (b) indicates the location where the extrusion deformation is most serious. The area of ​​the pole piece at this location is 3cm 2, thickness 5mm. Soak in 70% ethanol solution, adjust the solution pH to 6.5 with acetic acid, and soak in a 35℃ constant temperature box for 2 hours to remove residual fire-fighting fluid, surfactants, oil stains, etc. Filter and rinse alternately with anhydrous ethanol and deionized water 3 times until the filtrate pH is about 7.0. Transfer the above-treated electrode to a vacuum oven and dry it at 80℃ and 0.09Mpa relative vacuum for 24 hours. Transfer the above-dried block electrode to a planetary ball mill, put in agate grinding beads, and grind and disperse at a speed of 100r / min for 1 hour to obtain a loose electrode debris sample with coexistence of powder and flakes.

[0103] The electrode samples were then screened using a vertical multi-layer screening method, with mesh sizes of 20, 50 and 80 from top to bottom ( Figure 3 (a)). Figure 3 As shown in (b1), yellow and black mixed debris were separated and extracted on a 20-mesh standard sieve; from its scanning electron microscope micrograph ( Figure 3 (b2)) shows that the microstructure of the debris separated and extracted on the 20-mesh standard sieve is mainly a flaky structure; from its element spectrum detection diagram (3 (b3)), it can be seen that the main element of the debris separated and extracted on the 20-mesh standard sieve is Cu. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 20-mesh standard sieve is the copper current collector. Figure 3 As shown in (c1), black powder residue was separated and extracted on a 50-mesh standard sieve; from its scanning electron microscope micrograph ( Figure 3 (c2)) shows that the microstructure of the residue separated and extracted on the 50-mesh standard sieve is mainly spherical sintered blocks; from its element spectrum detection diagram ( Figure 3 (c3)) shows that the main elements of the debris separated and extracted on the 50-mesh standard sieve include Mn, Ni, Co, O, C, and P. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 50-mesh standard sieve is the debris sintered together by the spherical positive electrode materials. Figure 3 As shown in (d1), black powder residue was separated and extracted on a 80-mesh standard sieve; from its scanning electron microscope micrograph ( Figure 3 (d2)) shows that the microstructure of the debris separated and extracted on the 80-mesh standard sieve is mainly dispersed blocks and flakes; from its element spectrum detection diagram ( Figure 3 (d3)) It can be seen that the main element of the debris separated and extracted on the 80-mesh standard sieve is C. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 80-mesh standard sieve is the powdered and dispersed irregular flake graphite negative electrode material.

[0104] Take the copper current collector flake debris on the 20-mesh test sieve for testing. First, use a soft brush to wipe off the large pieces of black residual material remaining on the surface. Then, transfer it to anhydrous ethanol and ultrasonically disperse and clean the remaining black material on the surface of the copper foil for 1 hour. Transfer the above-treated electrode to a vacuum oven and dry it at 50°C and 0.09Mpa relative vacuum for 2 hours to ensure that the current collector is thoroughly dried. After polishing the surface of the copper foil with non-woven fabric, use a metallographic microscope to observe the structure. For comparative analysis, the current collector debris at a distance of 10 cm from the sampling position of the electrode was also taken and its structure was observed through the same treatment operation. From Figure 4 (a) It can be seen that the current collector of the squeezed electrode presents fine dendrites and equiaxed crystals as a whole, and a large amount of red cuprous oxide and black cupric oxide eutectic structures are distributed along the grain boundaries. The current collector far away from this point presents large-grained equiaxed crystals, and a small amount of red cuprous oxide and black cupric oxide eutectic structures are distributed along the grain boundaries ( Figure 4 (b)).

[0105] Take the debris powder sample on the 50-mesh test sieve and carry out X-ray powder diffraction test (XRD), and the test angle (2θ) range is selected from 10° to 80°. Figure 5 (a) It can be seen that the diffraction peak positions of the XRD spectra of the battery debris powder samples tested in three parallel experiments are consistent, indicating that the operation parallelism of this method is excellent. And the XRD crystal form spectrum of the normal battery positive electrode material ( Figure 5 (b)) XRD crystal spectra of normal battery negative electrode materials ( Figure 5 (c)) and XRD crystal spectra of copper materials ( Figure 5 (d)) can be seen from the comparison. The characteristic peaks near 36.8° and 44.5° in the XRD spectrum of the original battery positive electrode material still exist, but the diffraction peaks at 18.5°, 38.5°, 48.6° and 64.2° have disappeared. This is mainly due to the decomposition of the positive electrode material or the generation of a new material system caused by the reaction between the positive electrode and the electrolyte during the fire, which led to the change of the unit cell structure. The diffraction peak of graphite carbon corresponding to the 26.6° position in the XRD spectrum of the original battery negative electrode material is still there, indicating the presence of a large amount of residual carbon in the battery debris after the fire process, and the diffraction intensity of this peak is the highest. The diffraction characteristic peaks at 43.0°, 50.1°, and 73.8° in the XRD spectrum of copper still exist after the fire, but they all show a certain degree of rightward shift, indicating that the unit cell size of the copper component has become smaller after the thermal runaway process. By observation, such as Figure 5As marked in (a), on the XRD diagram of the sample after experiencing a thermal runaway fire process, the relative intensity of the newly added peaks from low angles to high angles in the range of 21° to 24° generally shows a trend of first increasing and then decreasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° generally shows an increasing trend, the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° generally shows a trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° generally shows a trend of approaching.

[0106] The powder residue on the 80-mesh test sieve was taken for Raman spectroscopy analysis. The laser wavelength used for Raman spectroscopy testing was 532nm. Figure 6 It can be seen that the diffraction peak positions of the carbon component characteristics of the Raman spectra of the battery debris powder samples tested in the three parallel experiments are basically consistent, indicating that the method has excellent parallel operation. The peak positions of the amorphous structure carbon (D peak) and graphitized carbon (G peak) of parallel sample 1 are located at 1355.8 cm -1 and 1585.0cm -1 After deducting the baseline, the relative intensities of the peaks are 1563.4 and 2159.8, respectively. The calculated ratio of the intensity of the G peak to the intensity of the D peak is 1.38. The peak positions of the amorphous carbon (D peak) and graphitized carbon (G peak) of parallel sample 2 are located at 1354.2 cm -1 and 1585.5cm -1 After deducting the baseline, the relative intensities of the peaks are 1301.2 and 2038.3, respectively. The calculated ratio of the intensity of the G peak to the intensity of the D peak is 1.56. The peak positions of the amorphous carbon (D peak) and graphitized carbon (G peak) of parallel sample 3 are located at 1356.0 cm -1 and 1585.2cm -1 , the relative intensities of the peaks after deducting the baseline were 1234.3 and 1830.9 respectively, and the calculated ratio of the intensity of the G peak to the intensity of the D peak was 1.48. The relative ratios of the intensity of the G peak to the intensity of the D peak obtained in the above three parallel tests were all between 1 and 2.

[0107] Based on the above test analysis results, the thermal runaway fire in the monomer was caused by a local internal short circuit.

[0108] Application Example 2

[0109] Taking a thermal runaway accident of a power battery during charging as an example, the extraction and analysis of the power battery monomer wreckage are as follows:

[0110] like Figure 7 As shown in the figure, remove the battery cell with the most serious burn. Figure 7(a) The battery cell shell is severely damaged and the pole piece is blown out. It has not been exposed to firefighting fluid, so there are no residual hard foam particles of firefighting fluid on the surface. Since a large number of pole pieces have been blown out, it is impossible to remove the pole pieces according to the extrusion direction of the pole pieces. Therefore, the pole pieces with more serious burns are removed for analysis. The area of ​​the pole piece at this position is 5cm 2 , thickness 5mm. Then, rinse alternately with anhydrous ethanol and deionized water 3 times. Transfer the above-treated electrode to a vacuum oven and dry it at 70°C and 0.09Mpa relative vacuum for 24 hours. Transfer the above-dried block electrode to a planetary ball mill, put in agate grinding beads, and grind and disperse at a speed of 100r / min for 1 hour to obtain a loose electrode debris sample with coexistence of powder and flakes. The electrode samples were then screened by vertical multi-layer screening method, and the mesh sizes from top to bottom were 20 mesh, 50 mesh and 80 mesh. Figure 8 As shown in (a1), yellow and black mixed debris were separated and extracted on a 20-mesh standard sieve; from its scanning electron microscope micrograph ( Figure 8 (a2)) shows that the microstructure of the debris separated and extracted on the 20-mesh standard sieve is mainly a flake structure; from its element spectrum detection diagram ( Figure 8 a3) It can be seen that the main element of the debris separated and extracted on the 20-mesh standard sieve is Cu. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 20-mesh standard sieve is the copper current collector. Figure 8 As shown in (b1), black powder residue was separated and extracted on a 50-mesh standard sieve; from its scanning electron microscope micrograph (Fig. Figure 8 (b2)) shows that the microstructure of the debris separated and extracted on the 50-mesh standard sieve is mainly spherical sintered blocks; from its element spectrum detection diagram ( Figure 8 (b3)) shows that the main elements of the debris separated and extracted on the 50-mesh standard sieve include Mn, Ni, Co, O, C, P and Al. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 50-mesh standard sieve is the debris of spherical positive electrode materials sintered together. Figure 8 As shown in (c1), black powder residue was separated and extracted on a 80-mesh standard sieve; from its scanning electron microscope micrograph ( Figure 8 From the element spectrum detection diagram (8(c3)), it can be seen that the main element of the debris separated and extracted on the 80-mesh standard sieve is C. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 80-mesh standard sieve is powdered and dispersed irregular flake graphite negative electrode material.

[0111] Take the copper current collector flake debris on the 20-mesh test sieve for testing. First, use a soft brush to wipe off the large pieces of black residual material remaining on the surface. Then, transfer it to anhydrous ethanol and ultrasonically disperse and clean the remaining black material on the surface of the copper foil for 1 hour. Transfer the above-treated electrode to a vacuum oven and dry it at 50°C and 0.09Mpa relative vacuum for 2 hours to ensure that the current collector is thoroughly dried. After polishing the surface of the copper foil with non-woven fabric, use a metallographic microscope to observe the structure. From Fig. 9 It can be seen that the densely distributed circular black spots on the copper foil are caused by the high current breakdown process.

[0112] Take the debris powder sample on the 50-mesh test sieve and carry out X-ray powder diffraction test (XRD), and the test angle (2θ) range is selected from 10° to 65°. Fig.10 It can be seen that the diffraction peak positions of the XRD spectra of the battery debris powder samples tested in the three parallel experiments are consistent, indicating that the method has excellent parallel operation. The diffraction peak of graphite carbon corresponding to the position of 26.5° in the XRD spectrum indicates the presence of a large amount of residual carbon in the battery debris after the fire process, and the diffraction intensity of this peak is the highest. By observation, such as Fig.10 Marked in the middle, on the XRD diagram of the sample after experiencing a thermal runaway fire process, the relative intensity of the newly added peaks in the range of 21°~24° is relatively weak and almost close, the relative intensity of the newly added peaks from low angles to high angles in the range of 29°~32° generally shows an obvious increasing trend, the relative intensity of the newly added peaks from low angles to high angles in the range of 33°~35° is weak, and the overall trend is first increasing and then decreasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38°~43° is strong, and the overall trend is obviously decreasing first and then increasing.

[0113] The powder residue on the 80-mesh test sieve was taken for Raman spectroscopy analysis. The laser wavelength used for Raman spectroscopy testing was 532nm. Fig.11 It can be seen that the diffraction peak positions of the carbon component characteristics of the Raman spectra of the battery debris powder samples tested in the three parallel experiments are basically consistent, indicating that the method has excellent parallel operation. The peak positions of the amorphous structure carbon (D peak) and graphitized carbon (G peak) of parallel sample 1 are located at 1357.5 cm -1 and 1577.3cm -1 After deducting the baseline, the relative intensities of the peaks are 381.6 and 3336.1, respectively. The calculated ratio of the intensity of the G peak to the intensity of the D peak is 8.74. The peak positions of the amorphous carbon (D peak) and graphitized carbon (G peak) of parallel sample 2 are located at 1362.4 cm -1 and 1578.6cm -1After deducting the baseline, the relative intensities of the peaks are 527.6 and 4447.5, respectively. The calculated ratio of the intensity of the G peak to the intensity of the D peak is 8.43. The peak positions of the amorphous carbon (D peak) and graphitized carbon (G peak) of parallel sample 3 are located at 1351.5 cm -1 and 1578.7cm -1 , the relative intensities of the peaks after deducting the baseline were 256.3 and 1589.5 respectively, and the calculated ratio of the intensity of the G peak to the intensity of the D peak was 6.20. The relative ratios of the intensity of the G peak to the intensity of the D peak obtained in the above three parallel tests were all between 6 and 9.

[0114] Based on the above test analysis results, the thermal runaway fire in the monomer was caused by overcharging.

[0115] Application Example 3

[0116] Taking a power battery in a thermal runaway accident as an example, the extraction and analysis of the power battery monomer wreckage are as follows:

[0117] like Fig.12 As shown in the figure, remove the battery cells that are severely burned. Fig.12 (a) It can be seen that the battery cell shell has been completely burned and has not been exposed to fire-fighting fluid, so there are no residual hard foam particles of fire-fighting fluid on the surface. According to the situation, the overall burning of the cell is relatively uniform. The pole piece at the middle position is taken out as shown in 12 (b). The area of ​​the pole piece at this position is about 5cm 2 , thickness 3mm. Then, rinse alternately with anhydrous ethanol and deionized water 3 times. Transfer the above-treated electrode to a vacuum oven and dry it at 80°C and 0.09Mpa relative vacuum for 24 hours. Transfer the above-dried block electrode to a planetary ball mill, put in agate grinding beads, and grind and disperse at a speed of 150r / min for 1 hour to obtain a loose electrode debris sample with coexistence of powder and flakes. The electrode samples were then screened by vertical multi-layer screening method, and the mesh sizes from top to bottom were 20 mesh, 50 mesh and 80 mesh. As Fig.13 As shown in (a1), black flaky debris was separated and extracted on a 20-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.13 (a2)) shows that the microstructure of the debris separated and extracted on the 20-mesh standard sieve is mainly a flake structure; from the element spectrum detection Fig.13 (a3) It can be seen that the main element of the debris separated and extracted on the 20-mesh standard sieve is Cu. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 20-mesh standard sieve is copper current collector. Fig.13 As shown in (b1), black powder residue was separated and extracted on a 50-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.13(b2)) shows that the microstructure of the debris separated and extracted on the 50-mesh standard sieve is mainly spherical sintered blocks; from its element spectrum detection diagram (13 (b3)), it can be seen that the main elements of the debris separated and extracted on the 50-mesh standard sieve include Mn, Ni, Co, O, C, P and Al. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 50-mesh standard sieve is the debris sintered together by spherical positive electrode materials. Fig.13 As shown in (c1), black powder residue was separated and extracted on a 80-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.13 (c2)) shows that the microstructure of the debris separated and extracted on the 80-mesh standard sieve is mainly dispersed flakes; from its element spectrum detection diagram (13 (c3)), it can be seen that the main element of the debris separated and extracted on the 80-mesh standard sieve is C. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 80-mesh standard sieve is powdered and dispersed irregular flake graphite negative electrode material.

[0118] Take the copper current collector flake debris on the 20-mesh test sieve for testing. First, use a soft brush to wipe off the large pieces of black residual material remaining on the surface. Then, transfer it to anhydrous ethanol and ultrasonically disperse and clean the remaining black material on the surface of the copper foil for 1 hour. Transfer the above-treated electrode to a vacuum oven and dry it at 50°C and 0.09Mpa relative vacuum for 2 hours to ensure that the current collector is thoroughly dried. After polishing the surface of the copper foil with non-woven fabric, use a metallographic microscope to observe the structure. From Fig.14 It can be seen that colorful ring patterns are found in the copper foil, which are traces left by the initial burning of the open flame.

[0119] Take the debris powder sample on the 50-mesh test sieve and carry out X-ray powder diffraction test (XRD), and the test angle (2θ) range is selected from 10° to 70°. Fig.15 It can be seen that the diffraction peak of graphite carbon corresponding to the position of 26.7° in the XRD spectrum indicates the presence of a large amount of residual carbon in the battery debris after the fire process, and the diffraction intensity of this peak is the highest. Fig.15 Marked in the middle, on the XRD diagram of the sample after experiencing a thermal runaway fire process, the relative intensity of the new peaks from low angles to high angles in the range of 21° to 24° shows a decreasing trend as a whole, and the relative intensity of the new peaks from low angles to high angles in the range of 29° to 32° shows an increasing trend as a whole, the relative intensity of the new peaks in the range of 33° to 35° is close, and the relative intensity of the new peaks in the range of 38° to 43° is close.

[0120] The powder residue on the 80-mesh test sieve was taken for Raman spectroscopy analysis. The laser wavelength used for Raman spectroscopy testing was 532nm. Fig.16 It can be seen that the peaks of amorphous carbon (D peak) and graphitized carbon (G peak) in the Raman spectrum of the carbon component characteristics of the experimental battery debris powder sample are located at 1351.9 cm-1 and 1576.3cm -1 After deducting the baseline, the relative intensities of the peaks are 375.3 and 4709.7 respectively. The calculated intensity ratio of the G peak to the D peak is 12.55, and the relative intensity ratio is higher than 10.

[0121] Based on the above test analysis results, the thermal runaway fire in the monomer was caused by ignition of open flames.

[0122] Application Example 4

[0123] Taking a power battery in a thermal runaway accident as an example, the extraction and analysis of the power battery monomer wreckage are as follows:

[0124] like Fig.17 As shown in the figure, the battery cell with severe burn damage was taken out. It has not been exposed to fire-fighting liquid, so no residual hard foam particles of fire-fighting liquid are seen on the surface. Take out the pole piece at the location with severe burn damage that is squeezed inward (as shown in the marked box in the figure). The area of ​​the pole piece at this location is about 4cm 2 , thickness 3mm. Then, rinse alternately with anhydrous ethanol and deionized water 3 times. Transfer the above-treated electrode to a vacuum oven and dry it at 80°C and 0.09Mpa relative vacuum for 24 hours. Transfer the above-dried block electrode to a planetary ball mill, put in agate grinding beads, and grind and disperse at a speed of 100r / min for 1 hour to obtain a loose electrode debris sample with coexistence of powder and flakes. The electrode samples were then screened by vertical multi-layer screening method, and the mesh sizes from top to bottom were 20 mesh, 50 mesh and 80 mesh. Fig.18 As shown in (a1), black and yellow large flakes of debris were separated and extracted on a 20-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.18 (a2)) shows that the microstructure of the debris separated and extracted on the 20-mesh standard sieve is mainly a flake structure; from the element spectrum detection Fig.18 (a3) It can be seen that the main element of the debris separated and extracted on the 20-mesh standard sieve is Cu. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 20-mesh standard sieve is copper current collector. Fig.18 As shown in (b1), black powder residue was separated and extracted on a 50-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.18 (b2)) shows that the microstructure of the debris separated and extracted on the 50-mesh standard sieve is mainly spherical sintered blocks; from its element spectrum detection diagram (18 (b3)), it can be seen that the main elements of the debris separated and extracted on the 50-mesh standard sieve include Mn, Ni, Co, O, C, P and Al. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 50-mesh standard sieve is the debris sintered together by spherical positive electrode materials. Fig.18As shown in (c1), black powder residue was separated and extracted on a 80-mesh standard sieve; from its scanning electron microscope micrograph ( Fig.18 (c2)) shows that the microstructure of the debris separated and extracted on the 80-mesh standard sieve is mainly dispersed blocks and flakes; from its element spectrum detection diagram ( Fig.18 (c3)) It can be seen that the main element of the debris separated and extracted on the 80-mesh standard sieve is C. Based on the above, it is confirmed that the main component of the debris separated and extracted on the 80-mesh standard sieve is the powdered and dispersed irregular flake graphite negative electrode material.

[0125] Take the copper current collector flake debris on the 20-mesh test sieve for testing. First, use a soft brush to wipe off the large pieces of black residual material remaining on the surface. Then, transfer it to anhydrous ethanol and ultrasonically disperse and clean the remaining black material on the surface of the copper foil for 1 hour. Transfer the above-treated electrode to a vacuum oven and dry it at 50°C and 0.09Mpa relative vacuum for 2 hours to ensure that the current collector is thoroughly dried. After polishing the surface of the copper foil with non-woven fabric, use a metallographic microscope to observe the structure. From Fig.19 It can be seen that the copper foil turns red uniformly as a whole.

[0126] Take the debris powder sample on the 50-mesh test sieve and carry out X-ray powder diffraction test (XRD), and the test angle (2θ) range is selected from 10° to 65°. Fig. 20 It can be seen that the diffraction peak of graphite carbon corresponding to the position of 26.5° in the XRD spectrum indicates the presence of a large amount of residual carbon in the battery debris after the fire process, and the diffraction intensity of this peak is the highest. Through observation, the relative intensity of the peaks added from low angles to high angles in the range of 21° to 24° on the XRD graph of the sample after the thermal runaway fire process shows an overall trend of first increasing and then decreasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° shows an overall increasing trend, and the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° shows an overall trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° shows an overall decreasing trend.

[0127] The powder residue on the 80-mesh test sieve was taken for Raman spectroscopy analysis. The laser wavelength used for Raman spectroscopy testing was 532nm. Fig.21 It can be seen that the peak positions of amorphous carbon (D peak) and graphitized carbon (G peak) in the Raman spectrum of the carbon component characteristics of the experimental battery debris powder sample are located at 1354.1 cm -1 and 1578.9cm -1 After deducting the baseline, the relative intensities of the peaks are 814.3 and 2923.1 respectively. The calculated intensity ratio of the G peak to the D peak is 3.58, and the relative intensity ratio is between 3 and 5.

[0128] Based on the above test analysis results, the cause of the thermal runaway fire in the monomer was due to thermal runaway triggered by overheating.

[0129] Combining the above-mentioned application examples, it can be seen that the present invention has the following advantages and effects compared with the prior art:

[0130] (1) The method for extracting thermal runaway debris and determining the cause of new energy vehicle power battery thermal runaway provided by the present invention systematically combines the on-site investigation of new energy vehicle fire accidents with laboratory analysis and detection technology, providing technical support for the analysis and detection of power battery debris in fire accident investigations, and effectively improving the current new energy vehicle fire accident investigation system, making it easier for relevant accident investigators to conduct new energy vehicle fire accident investigations and effectively determine the causes of accidents.

[0131] (2) The present invention provides a method for extracting and determining the cause of thermal runaway debris of power batteries for new energy vehicles, and invents a power battery debris extraction technology. After battery disassembly, monomer selection, debris electrode sampling, impurity removal, alcohol solution immersion to remove fire liquid, ball milling and vertical multi-layer screening, the battery electrode debris that has experienced a fire accident can be effectively separated according to different main material components, solving the problem of difficulty in extracting materials for analysis and research after sintering the battery electrode after a fire accident. The method is suitable for investigations of various fire accidents caused by thermal runaway of lithium-ion battery systems, and has the characteristics of easy operation, high efficiency and strong applicability.

[0132] (3) The method for extracting thermal runaway debris from power batteries of new energy vehicles and determining the cause of the accident is based on the metallographic analysis technology of the residual copper current collector, the material crystal structure analysis technology and the material carbon composition analysis technology, and clarifies the image features or parameter thresholds for determining different triggering methods. This is of great significance for improving the effectiveness of the investigation of the cause of new energy vehicle fire accidents and studying the occurrence patterns of new energy vehicle fires.

[0133] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for extracting thermal runaway debris from power batteries of new energy vehicles and determining the cause of the thermal runaway, characterized in that: The method comprises: Investigate sampling procedures to obtain battery electrodes after fire incidents; The debris extraction step is to separate and extract the debris materials of the battery pole pieces obtained in the investigation and sampling step, so as to separate the battery pole piece debris that has experienced the fire accident according to different main material components and obtain battery pole piece debris with different particle sizes. a step of analyzing the structure of the residual current collector, screening out the battery pole piece debris that meets a first particle size value from the battery pole piece debris of different particle sizes, wherein the battery pole piece debris that meets the first particle size value is a copper current collector, treating the copper current collector, observing the structure of the treated copper current collector with a metallographic microscope, and analyzing the metallographic microstructure of the copper foil to analyze the cause of the thermal runaway accident; The step of analyzing the crystal structure of the powder of the debris material is to select the battery pole pieces that meet the second particle size value from the battery pole pieces of different particle sizes to carry out X-ray powder diffraction test, and analyze the conditions that have caused thermal runaway based on the test spectrum; The material carbon component analysis step is to select the battery pole piece debris that meets the third particle size value from the battery pole piece debris of different particle sizes for Raman spectroscopy analysis, and analyze and infer the thermal runaway conditions that have occurred based on the Raman spectrum.

2. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 1, characterized in that: The survey sampling steps include: Remove the power battery pack that has experienced the fire accident from the vehicle, cut off the electrical connection lines, and then disassemble the battery pack; Observe the fire area, remove the most severely burned module, dismantle the module casing, and remove the internal battery cells; Observe the deformation characteristics of the entire battery cell group inside the module, and remove the battery cell that is most severely squeezed and deformed in the module or the battery cell that is initially determined to be the trigger point through fire trace analysis at the accident site; Remove the single body shell, take out the pole piece at the location with severe burning inside, and if the burning situation is not much different, take out the pole piece in the area with the most serious extrusion and deformation; if the accident power battery has been extinguished with fire water, first remove the particulate matter remaining on the pole piece, and then take out the pole piece at the location with severe burning inside.

3. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 1 or 2, characterized in that: The battery pole pieces obtained in the investigation and sampling step are subjected to separation and extraction of the debris materials, so as to separate the battery pole piece debris that has experienced the fire accident according to different main material components, and obtain battery pole piece debris of different particle sizes, including: Soak the battery pole pieces after the fire accident in a 30℃~35℃, 50%~70% concentration ethanol solution, and adjust the solution pH value to 6.0±0.5 with acetic acid; after soaking for 2~3 hours, filter, and rinse with anhydrous ethanol and ionized water alternately for no less than 3 times until the filtrate pH value is about 7.0; The battery pole piece after the above treatment is transferred to a vacuum oven and dried at 50°C to 80°C and a relative vacuum degree of 0.06 to 0.09 MPa for 24 hours to ensure that the pole piece debris is completely dried; The dried block-shaped battery pole pieces are transferred into a planetary ball mill, agate grinding beads are placed in the mill, and the powder and flake-like loose pole piece debris samples are obtained at a speed of 100 r / min to 150 r / min for 1 to 2 hours. Then, a vertical multi-layer screening method is used to screen the loosely dispersed pole piece debris from top to bottom in the order of 20 mesh, 30 mesh, 50 mesh, 60 mesh or 80 mesh, and the loosely dispersed pole piece debris are separated according to the particle size of ≥0.9 mm, 0.9 mm to 0.6 mm, 0.6 mm to 0.355 mm, 0.355 to 0.3 mm or 0.3 to 0.2 mm.

4. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 1, characterized in that: The processing of the copper current collector comprises: The black positive / negative electrode materials remaining on the surface of the copper current collector are wiped off, and then transferred to anhydrous ethanol, and the remaining black substances on the surface of the copper current collector are cleaned by ultrasonic dispersion. The cleaned copper current collector is moved to a vacuum oven for drying; the surface of the dried copper current collector is polished.

5. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 1, characterized in that: The cause analysis of thermal runaway accidents through metallographic microstructure analysis of copper foil includes: If circular black spots are found on the copper foil through observation, it is caused by a high current breakdown process; if the area of ​​the circular black spots is smaller than the preset value and appears densely, it is judged that thermal runaway caused by overcharging has occurred there; If there are small dendrites or equiaxed crystals in a location in the copper foil, and large equiaxed crystals are scattered around other locations, it means that this location has experienced the highest temperature during the thermal runaway process and is also the location where the temperature drops the earliest and the drop rate is the fastest. Therefore, it is judged that this location is the initiation site of the local internal short circuit. If there are colorful ring patterns in the copper foil, it is the trace left by the initial flame burning, which means that there has been thermal runaway caused by open flames. If the copper foil shows an overall uniform color change, it is judged that the area has been heated and overheated, causing thermal runaway.

6. The method for extracting thermal runaway debris and determining the cause of the new energy vehicle power battery according to claim 3, characterized in that: The method of screening out battery pole piece debris that meets the second particle size value and conducting X-ray powder diffraction testing includes: The battery pole piece powder residues on the 30-mesh or 50-mesh test sieve are screened out for X-ray powder diffraction testing. The scanning angle range during the test must be at least 20° to 43°.

7. The method for extracting thermal runaway debris and determining the cause of the new energy vehicle power battery according to claim 6, characterized in that: The analysis of the thermal runaway conditions that have occurred based on the test map includes: If the relative intensity of the newly added peaks in the range of 21° to 24° is close, the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, the relative intensity of the newly added peaks from low angle to high angle in the range of 33° to 35° shows an increasing trend first and then decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 38° to 43° shows a decreasing trend first and then increasing trend as a whole, it is judged that thermal runaway caused by overcharging has occurred at this location; If the relative intensity of the newly added peaks from low angle to high angle in the range of 21° to 24° shows an overall trend of increasing first and then decreasing, the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angle to high angle in the range of 33° to 35° shows an overall trend of decreasing first and then increasing, and the relative intensity of the newly added peaks from low angle to high angle in the range of 38° to 43° shows an overall trend of approaching, it is judged that thermal runaway caused by local internal short circuit has occurred at this location; If the relative intensity of the newly added peaks from low angle to high angle in the range of 21° to 24° shows a decreasing trend as a whole, and the relative intensity of the newly added peaks from low angle to high angle in the range of 29° to 32° shows an increasing trend as a whole, and the relative intensity of the newly added peaks in the range of 33° to 35° is close, and the relative intensity of the newly added peaks in the range of 38° to 43° is close, it is judged that thermal runaway caused by fire has occurred at this location; If the relative intensity of the newly added peaks from low angles to high angles in the range of 21° to 24° shows an overall trend of first increasing and then decreasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 29° to 32° shows an overall trend of increasing, the relative intensity of the newly added peaks from low angles to high angles in the range of 33° to 35° shows an overall trend of first decreasing and then increasing, and the relative intensity of the newly added peaks from low angles to high angles in the range of 38° to 43° shows an overall trend of decreasing, it is judged that thermal runaway caused by overheating has occurred at this location.

8. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 3, characterized in that: The method of screening out battery pole piece debris meeting the third particle size value and conducting Raman spectroscopy analysis includes: The battery pole powder residues on the 60-mesh or 80-mesh test sieve were screened out for Raman spectroscopy analysis. -1 and 1580±10cm -1 The carbon Raman active peaks that appear nearby are the objects of analysis and research, which correspond to the D peak of amorphous carbon structure and the G peak of graphitized carbon respectively. The relative ratio of the intensity of the G peak to the intensity of the D peak is used to analyze and infer the conditions that caused thermal runaway that occurred there.

9. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 8, characterized in that: The analysis and inference of the thermal runaway-inducing conditions that occurred at the location based on the relative ratio of the intensity of the G peak to the intensity of the D peak includes: If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 1 and 2, it is judged that thermal runaway caused by a local internal short circuit has occurred at that location; If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 3 and 5, it is judged that thermal runaway caused by overheating has occurred at this location; If the relative ratio of the intensity of the G peak to the intensity of the D peak is between 6 and 9, it is judged that thermal runaway caused by overcharging has occurred at this location; If the relative ratio of the intensity of peak G to the intensity of peak D is greater than 10, it is judged that thermal runaway caused by fire has occurred at that location.

10. The method for extracting thermal runaway debris and determining the cause of a new energy vehicle power battery according to claim 3, characterized in that: The vertical multi-layer screening method refers to stacking a series of standard sieves with different apertures or different mesh sizes vertically from top to bottom in the order of decreasing aperture or increasing mesh size for screening.

Citation Information

Patent Citations

  • Method and device for determining short-circuit point, and electronic device

    CN108344919A

  • Method for deducing cause of thermal runaway of battery

    CN114624592A

  • Lithium battery thermal runaway inducement identification method and system

    CN115575830A

  • New energy automobile fire reason analysis and judgment method

    CN115752586A

  • Method for studying and judging cause of thermal runaway accident of fault cell of power battery

    CN115790899A

Cited By

  • Lithium ion battery thermal runaway inducement tracing method and device based on particulate matter morphology

    CN121459062A